Intersectoral flows in the economies of the Visegrad Group countries - Michał Przybyliński; Joanna Trębska (Comparative Economic Research. Central and Eastern Europe, 2023)
We present a comparative study of flows between institutional sectors in the economies of Czechia, Hungary, Poland and Slovakia, with particular emphasis on the role of the foreign sector. The purpose of our study is to determine the strength and nature of inter-sectoral ties in the analyzed countries and point out the similarities and differences between them. The research method is based on the sequence of all transactions included in the System of National Accounts (SNA): product transactions, primary income generation and allocation, income distribution, and financial instrument transactions. The study is distinguished by its consistency and balance within the SNA. The method used to transform data into a payer-payee matrix guarantees the preservation of these properties. It creates a new perspective for assessing the sensitivity of economies to external processes. It is the first such comprehensive comparative study, providing unambiguous and replicable results based on a standardized accounting system that operates in all European countries. The period covered by the study (2000-2020) allows us to draw interesting conclusions about the processes that took place during and after the accession to the European Union. The results indicate, inter alia, an increase in the involvement of the foreign sector, primarily in production processes (import, export) and investment. Particularly noteworthy is the high degree of financialization of the Hungarian economy.
Keywords: 330; Visegrad Group Countries; flow of funds; system of national accounts; institutional sectors